The Twin Self-Delusions of IR: Why 'Hierarchy' and Not 'Anarchy' is the Core Concept of IR. (June 2014) - Hobson, John M
This article deconstructs the twin 'self-delusions' of IR to reveal, first, the conventional axiom that the discipline enquires into juridically-equal sovereign state relations under international anarchy masks the dark hierarchical face of IR which promotes, defends and reifies, analytically and/or normatively, Western civilisation over non-Western states, and, second, the conventional axiom that IR operationalises a positivist and/or value-free cultural pluralism masks the dark face of Eurocentric monism that constitutes the core ideological foundation of the vast majority of IR theory. These emerge from IR theory's deployment of the twin concepts of Eurocentric hierarchy and the Eurocentric 'standard of civilisation', which yield the twin conceptions of 'formal (imperialist) hierarchy' and 'informal (anti-imperialist) hierarchy' alongside the notion of 'gradated sovereignties' in world politics. To illustrate this, the 'formal-hierarchical' conception is traced in classical English School pluralism and neorealist hegemonic stability, while the 'informal-hierarchical' conception is traced in neo-Marxism and classical English School pluralism.